A theory-based intervention to reduce alcohol drinking in excess of guideline limits among undergraduate students - Hagger, Martin; Lonsdale, A.; Chatzisarantis, N. (John Wiley & Sons Ltd., 2012)
Objectives: Undergraduate students frequently exceed guideline limits for alcohol intake in a single session and are highly susceptible to associated health, social, and economic problems. Psychological theory suggests that interventions aimed at reducing alcohol consumption should target both motivational and volitional phases of action to be effective. This study reports an integrated theory-based intervention aimed at reducing undergraduates’ alcohol consumption in excess of guideline limits. Design: The study adopted a 2 (motivation: mental simulation vs. no mental simulation) × 2 (volitional: implementation intention vs. no implementation intention) randomized controlled design presented in an online format. Methods: Undergraduate students (N= 238; females, n= 133, M age = 20.11, SD= 2.09; males, n= 105, M age = 20.38, SD= 1.35) completed baseline psychological measures and self-reported alcohol consumption as units consumed and heavy episodic drinking occasions followed by the intervention manipulation (if any). One month later participants completed follow-up measures of the psychological variables and alcohol consumption.Results: Significant reductions in alcohol consumption were observed at follow-up. Participants receiving a mental simulation intervention reported significantly fewer units of alcohol consumed and heavy episodic drinking occasions. Among participants with high baseline alcohol consumption, participants in the combined mental simulation and implementation intention intervention group consumed significantly fewer units than other groups. Conclusion: Results support the use of these theory-based strategies to reduce alcohol drinking in excess of guideline limits among undergraduates. There was preliminary support for the interaction between the two strategies among heavier drinkers. Targeting both motivational and implemental phases of action poses a high probability for success in changing alcohol-related behaviour in this population.